Quantitative Analysis and Band Gap Determination for CIGS Absorber Layers Using Surface Techniques - Yun Jung Jang; Jihye Lee; Kang-Bong Lee; Donghwan Kim; Yeonhee Lee (Journal of Analytical Methods in Chemistry)
Recently, Cu(InXGa(1−X))Se2 (CIGS) absorber layers have been extensively studied by many research groups for thin-film solar cell technology. CIGS material is particularly promising due to its exceptionally high absorption coefficient and large band gap range, which is adjustable as a function of alloy stoichiometry. To enhance the conversion performance of CIGS solar cells, understanding the CIGS structure and composition is a crucial challenge. We conducted a quantitative study to determine the bulk composition of the major elements such as Cu, In, Ga, and Se of four different CIGS photovoltaic cells. The compositional information was obtained by X-ray fluorescence (XRF), inductively coupled plasma atomic emission spectroscopy (ICP-AES), and femtosecond laser ablation inductively coupled plasma mass spectrometry (fs-LA-ICP-MS). Then, the XRF concentration ratio was compared with the intensity ratio of fs-LA-ICP-MS to investigate the potential of accurate and rapid analysis using the fs-LA-ICP-MS technique. In contrast to the bulk information, the surface techniques can supply detailed information about the chemical composition across the depth profile. Here, elemental depth distributions of CIGS thin films were investigated using magnetic sector secondary ion mass spectrometry (SIMS) and Auger electron spectroscopy (AES). The atomic distributions of four different CIGS absorber layers exhibited a good agreement although they were obtained using two different surface instruments, AES and SIMS. Comparative analysis results of different CIGS absorber layers using SIMS, AES, and fs-LA-ICP-MS provide us with the appropriate technique for the information of accurate composition in a rapid analysis time. Thanks to a simple approach using the Ga/(In + Ga) ratio, the optical band gap energy of the Cu(InXGa(1−X))Se2 quaternary layer was monitored in the entire CIGS layer. The elemental distribution and the band gap determination were then used to elucidate their relationship to the corresponding CIGS cell efficiency result.